Effectiveness of Sandbox Curriculum Development from Work-Based Learning Management to Enhance Student’s Learning Competency, Learning Achievement, and Satisfaction for Grade 4 Students - Keeratichamroen, Wasana (Ratchaphruek Journal, 2025)
The purpose of this study were to 1) compare learning competency of students between before and after learning from sandbox curriculum using work-based learning, 2) compare learning achievement of students between before and after learning from sandbox curriculum using work-based learning, 3) compare learning achievement of students after learning from sandbox curriculum using work-based learning with a criterion of 70 percent, and 4) compare learning satisfaction of students between before and after learning from sandbox curriculum using work-based learning. The sample group of this study was 27 students of grade 4. Cluster random sampling was used to choose the sample. The tools used for the research were sandbox curriculum using work-based learning, a learning competency assessment, an achievement test, and learning satisfaction questionnaires. The data were statistically analyzed by percentage, mean, standard deviation and t-test. The findings of this research were as followed: 1) learning competency after learning from sandbox curriculum using work-based learning was significantly higher than before learning at .01 level, 2) learning achievement after learning from sandbox curriculum using work-based learning was significantly higher than before learning at .01 level, 3) learning achievement after learning from sandbox curriculum using work-based learning was significantly higher than 70 percent criterion at .01 level, and 4) learning satisfaction after learning from sandbox curriculum using work-based learning was significantly higher than before learning at .01 level.